The Management of Projects is Improved Through Enterprise Architecture on Project Management Application Systems - Hindarto, Djarot (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
From planning to execution, effective project management necessitates a holistic approach that incorporates various aspects. Enterprise Architecture has emerged as a promising method for enhancing project management in the modern era of business complexity. This article examines how employing Enterprise Architecture principles in project management can yield significant benefits. Enterprise Architecture enables project managers to comprehend the interdependencies between the various organizational components by adopting an approach that views the organization as an integrated whole. This improves planning, identification of prospective risks, and more precise decision-making. In addition, Enterprise Architecture provides a holistic view of the technology infrastructure and enterprise architecture, allowing project managers to identify opportunities to optimize extant resources. Moreover, Enterprise Architecture can enhance collaboration between project teams and other departments. Comprehending the interrelationships between organizational components makes communication and problem-solving more efficient. Enterprise Architecture also contributes to designing more adaptable and scalable initiatives, allowing them to better adapt to changing environments. This article investigates actual case studies of organizations that have adopted an Enterprise Architecture approach to project management. As evidence that Enterprise Architecture can be an asset in attaining project objectives, several benefits will be outlined, ranging from cost reduction to increased efficiency. By combining established project management methodologies with Enterprise Architecture principles, professionals can adopt a more comprehensive and strategic approach to attaining successful project outcomes.